Virtual Reality in Healthcare: Users’ Evaluation and Willingness to Disclose Health-Related Information - Augustin, Angelika (My University, 2025)
This study explores the intersection of virtual reality (VR) and metaverse technologies within the healthcare sector, addressing a critical gap in understanding users’ evaluation on applications within the healthcare sector and their derived privacy concerns impacting their willingness to disclose sensitive health information. As healthcare increasingly adopts digital innovations, VR presents a patient-centered approach that enhances treatment efficiency and accessibility. Despite the growing interest and application of VR in medical training, rehabilitation, and mental health, existing research lacks a nuanced examination of information disclosure behavior related to health information in this context. To address this gap, the study employs a systematic literature review to assess the current state of VR and metaverse applications in healthcare. Following this, qualitative interviews are conducted to gather insights on user evaluations of these technologies and their implications for information disclosure. The findings highlight the antecedents and outcomes of privacy concerns impacting information disclosure behavior, particularly in VR-based psychological therapy, providing both theoretical contributions to information systems research and practical recommendations for policymakers, healthcare providers, and technology developers. By emphasizing user-centered design and context-specific data protection frameworks, this research lays the groundwork for future inquiry into the responsible implementation of VR technologies in healthcare.
Keywords: virtual reality, metaverse, healthcare, information privacy, privacy, concerns, information disclosure